2021
DOI: 10.1177/26345161211021772
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Gastroesophageal Reflux Disease: Surgical Perspective from a Multi-Disciplinary Practice

Abstract: From the medical perspective, "refractory" gastroesophageal reflux disease (GERD) is symptomatic pathologic acid reflux that is not responsive to medical management, usually in the form of proton pump inhibitors (PPI). The basis of this approach is not to eliminate volume reflux, but to make reflux imperceptible by eliminating the stomach's ability to produce acid. Refractory, in this view, means that elimination of gastric acid does not lead to elimination of symptoms. GERD is protean in its manifestations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Holcomb et al [22] conducted a study about the Impact of psychiatric disorders on patient satisfaction after Nissen Fundoplication and concluded that anxiety and depression affect the patient's satisfaction on the long term follow up. Similarly, Grimsley et al [23] reported that psychological disorders, such as anxiety and depression, can also lead to poor out-come after Nissen fundoplication.…”
Section: Discussionmentioning
confidence: 95%
“…Holcomb et al [22] conducted a study about the Impact of psychiatric disorders on patient satisfaction after Nissen Fundoplication and concluded that anxiety and depression affect the patient's satisfaction on the long term follow up. Similarly, Grimsley et al [23] reported that psychological disorders, such as anxiety and depression, can also lead to poor out-come after Nissen fundoplication.…”
Section: Discussionmentioning
confidence: 95%